2022
DOI: 10.1002/ppul.26082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow rate on the end‐expiratory lung volume in infants with bronchiolitis using high‐flow nasal cannula evaluated through electrical impedance tomography

Abstract: Objectives: To evaluate the effects of four flow rates on the functional residual capacity (FRC) and pulmonary ventilation distribution while using a high-flow nasal cannula (HFNC).Working Hypothesis: Our hypothesis is that flow rates below 1.5 L•kg −1 •min −1 lead to FRC loss and respiratory distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the two studies involving infants with bronchiolitis, an increase in flow was associated with an improvement in the patient's S pO 2 / F IO 2 ratio ( supplementary table S4 ) [ 7 , 8 ]. When the flow was increased from 0.5 to 2 L·kg −1 ·min −1 [ 44 , 46 ], no significant differences were observed in V T and minute ventilation, as assessed by respiratory inductance plethysmography [ 45 ], pneumotachography [ 44 ] or electric impedance tomography [ 46 ].…”
Section: The Effects Of Different Flow Settings In Young Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…In the two studies involving infants with bronchiolitis, an increase in flow was associated with an improvement in the patient's S pO 2 / F IO 2 ratio ( supplementary table S4 ) [ 7 , 8 ]. When the flow was increased from 0.5 to 2 L·kg −1 ·min −1 [ 44 , 46 ], no significant differences were observed in V T and minute ventilation, as assessed by respiratory inductance plethysmography [ 45 ], pneumotachography [ 44 ] or electric impedance tomography [ 46 ].…”
Section: The Effects Of Different Flow Settings In Young Childrenmentioning
confidence: 99%
“…When the flow was increased from 0.5 to 2 L·kg −1 ·min −1 [ 44 , 46 ], no significant differences were observed in V T and minute ventilation, as assessed by respiratory inductance plethysmography [ 45 ], pneumotachography [ 44 ] or electric impedance tomography [ 46 ]. Moreover, when flow was increased from 0.4 to 2 L·kg −1 ·min −1 , a reduction in respiratory rate was observed in six studies ( figure 3a ) [ 6 , 8 , 43 46 ], except for the study conducted by N ascimento et al [ 7 ], in which no significant differences in respiratory rate were observed across flows of 0.5–2 L·kg −1 ·min −1 when using the Vapotherm device.…”
Section: The Effects Of Different Flow Settings In Young Childrenmentioning
confidence: 99%
See 2 more Smart Citations